Disrupting ACE2 Dimerization Mitigates the Infection by SARS-CoV-2 Pseudovirus - Zhu, Jiaqi; Su, Yue; Tang, Young (Frontiers in Virology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has caused over 6 million death and 500 million reported cases globally. More effective antiviral medications are needed to curb the continued spread of this disease. The infection by SARS-CoV-2 virus is initiated via the interaction between the receptor binding domain (RBD) of the viral glycoprotein Spike (S protein) and the N-term peptidase domain (PD) of the angiotensin-converting enzyme 2 (ACE2) expressed on host cell membrane. ACE2 forms protein homodimer primarily through its ferredoxin-like fold domain (aka. Neck-domain). We investigated whether the dimerization of ACE2 receptor plays a role in SARS-CoV-2 virus infection. We report here that the ACE2 receptor dimerization enhances the recognition of SARS-CoV-2 S protein. A 43 amino acid peptide based on the N-term of Neck-domain could block the ACE2 dimerization and hence the interaction between RBD and ACE2, and mitigate the SARS-CoV-2 S protein pseudotyped virus/host cell interaction. Our study illustrated a new route to develop potential therapeutics for the prevention and treatment of SARS-CoV-2 viral infection.